Integrin antagonists as potential therapeutic options for the treatment of Crohn's disease. (3rd March 2016) - McLean, Leon P.; Cross, Raymond K.
ABSTRACT: Introduction : Anti-integrin therapy for the treatment of patients with Crohn's disease is rapidly evolving. Two agents, natalizumab and vedolizumab, are approved by the United States Food and Drug Administration for the treatment of Crohn's disease, with vedolizumab the primary anti-integrin used due to a more favorable safety profile. Several other anti-integrins are in various stages of development. Areas Covered : This review discusses the current state of anti-integrin therapy as well as suggestions for positioning of these agents in clinical practice. Emerging anti-integrin therapies, their underlying mechanisms of action, and available safety and clinical data are also reviewed. Expert Opinion : Anti-integrins are effective for the treatment of Crohn's disease, even in patients refractory to other therapies. Their use should be considered in patients with Crohn's disease who do not respond to, develop non-response to, or have contraindications to anti-TNF therapy. Anti-integrin therapies can be offered as a first biologic therapy, in particular for older patients, patients with concurrent multiple sclerosis (natalizumab only), and in patients with contraindications to anti-TNF therapy. In patients with more severe symptoms, providers should consider co-induction with corticosteroids if possible to hasten remission.